Characteristics of patients with blastemal-type Wilms’ tumour - Hajzler, Weronika; Kopera, Joanna; Kosek, Klaudia; Mazur, Dorota; Rurańska, Iwona; Szczepański, Tomasz; Pobudejska-Pieniążek, Aneta (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Wilms’ tumour (nephroblastoma) is the most common malignant tumour of kidney in children and one of the 2 most common solid tumours located outside of the central nervous system. Nephroblastoma has a very good prognosis, but some histological types like blastemal-type require qualification to a high-risk group and intensification of treatment. We present the cases of 3 children diagnosed with nephroblastoma, blastemal-type. The first girl’s treatment was unsuccessful, as there were 4 cancer recurrences. The second girl had primarily metachronous form of nephroblastoma, but during recurrence the blastemal-type was diagnosed. Despite intensive treatment, it ended with failure. The third girl had a tumour in the left kidney, which was transformed from the bilateral nephroblastomatosis. She remains in remission; the therapy ended on February 2018.